Evaluating the effect of acute ammonia toxicity in a freshwater ecological environment on the growth and hematological functioning of Clarias gariepinus - Udume Bethel Uchenna; Ota Henry Obiahu; Zhifeng Yan; Onyewuchi Chidi Chikeziri (Aqua, 2022)
This study was carried out to evaluate the effect of ammonia toxicity on the growth and hematology of Clarias gariepinus. The mean weight gain of fish 1.52 ± 0.3 g was investigated under laboratory conditions at static bioassay for 96 h and 14 days, respectively. Five treatments of 96 h median lethal concentration LC50 were used, namely, T0 (0.00 g·l−1), T1 (0.40 g·l−1), T2 (0.60 g·l−1), T3 (0.80 g·l−1) and T4 (1.00 g·l−1), and each of these treatment concentrations was replicated three times for both toxicity exposures. The results clearly revealed that 96 h median lethal concentration (LC50) at treatments T4 (4.00), T3 (3.00), T2 (2.00) and T0 (0.00) g·l−1 gave an average mean value of 3.02 ± 0.02 g·l−1 with upper and lower limits of 6.28 and 1.42 g·l−1, respectively. The overall percentage mortality showed more than 71% of fish mortality at T4. Values for the 14-day sub-acute exposures to ammonia concentrations of T4 (1.00), T3 (0.80), T2 (0.60) and control (0.00) g·l−1 were also obtained. Growth indices indicated significant decreases (P<0.05) in the total feed intake (TFI), specific growth rate (SGR), mean weight gain and food conversion ratio (FCR) compared with the control. HIGHLIGHTS Increase in the lethal concentration of NH3 was principally responsible for the hematological modification of fish.; Growth indices indicated significant decreases (P < 0.05) in the total feed intake (TFI).; A strong relationship between NH3 toxicity and increase in fish mortality existed.; High levels of heavy metals can affect water quality and pose health risks.; Heavy metal concentrations in water were high enough to be of concern.;